KERANGKA BUDAYA DALAM PENELITIAN AKUNTANSI: DARI TEORI VIRTUE ETHICS MENUJU KESEJAHTERAAN PSIKOLOGIS INDIVIDU - Udin Saepudin (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2026)
This conceptual paper investigates the paradigm shift in accounting research by integrating cultural frameworks, moving from virtue ethics to psychological well-being. Despite rigorous formal internal controls, corporate governance failures remain prevalent due to managerial ethical misconduct. This study synthesizes the Five Constant Virtues of Confucianism (Ren, Yi, Li, Zhi, Xin) and Indonesian indigenous wisdom (Pancawaluya) as informal institutions that serve as ethical substitutes. Furthermore, the paper establishes a link between these cultural virtues and individual psychological resources, namely Psychological Capital (PsyCap) and Psychological Well-Being (PWB). Drawing on recent literature, including governance structures in Indonesia, this study proposes a holistic model where internalizing cultural values strengthens ethical resilience and audit performance